Pengaruh Perlakuan Pengarangan dan Penambahan Partikel Kemiri Terhadap Kualitas Paving Block ( - Frederick Raymond; Tito Sucipto; Irawati Azhar (Peronema Forestry Science Journal, 2015)
This experiment aims to determine the quality paving block with the addition of kemiri particles with carbonization treatment, evaluate the effect of adding particles and carbonization treatment and determine the number of particles and optimal treatment. Variations of these purpose was the particle composition (5%, 7%, 9%) and carbonization treatment. Characteristics of the paving block with treatments based on SNI 03-0691-1996 particle composition and carbonization treatment is from 24,21 to 62,53 MPa compressive strength (quality A-B), water absorption 1,89% - 2,79% (quality A), resistance to sodium sulfate 1,72% -2,82% (defects) and porosity of 1,31% - 5,67%. The treatment takes significant effect on the compressive strength, resistance to sodium sulfate and porosity but did not significantly affect the water absorption. Based on the results of analysis of variance, optimal treatment is the particle composition 7% with treatment without carbonization.Keywords: paving blocks, kemiri shell, carbonization, particle composition, quality.